Enhancing moisture transfer in vacuum membrane dehumidification via a Multi-Inlet approach - Abdullah, Shekh; Zubir, Mohd Nashrul Bin Mohd; Muhamad, Mohd Ridha Bin; Newaz, Kazi Md Salim; Alam, Md Shadab; Shaikh, Kaleemullah; Öztop, Hakan Fehmi (Elsevier, 2025)
This study addresses the need for a cost-effective and energy-efficient air conditioning system, especially in the context of global warming. While traditional vapor compression systems are commonly used, evaporative cooling systems present a potential alternative but struggle in high humidity environments. Recent advancements have incorporated independent dehumidification systems, such as desiccant and membrane-based methods. However, desiccant dehumidification requires significant energy for material regeneration, reducing its efficiency. Vacuum membrane dehumidification (VMD) presents a promising solution by selectively removing moisture from the air without the need for thermal energy input. In this study, a vacuum membrane-based dehumidification system was developed using nanomaterials and hygroscopic polymers, specifically titanium dioxide (TiO2) and polyvinyl alcohol (PVA) with potassium formate (KCOOH), to enhance membrane functionality. The research focused on improving moisture transfer in flat plate VMD through enhanced flow configurations. An experimental test bench was designed to control and monitor temperature and humidity during the dehumidification process. By implementing a multi-inlet mechanism in the membrane module, moisture removal increased by 55 % at 25 degrees C and 57 % at 28 degrees C, both at 90 % relative humidity. These results indicate that enhanced airflow and membrane surface modifications significantly improve mass transfer rates in VMD systems. Consequently, vacuum membrane dehumidification shows great potential as an energy-efficient alternative to conventional cooling methods, particularly in humid climates.
Keywords: Membrane Synthesis; Vacuum Membrane Dehumidification; Mass Transfer Enhancement; Independent Dehumidification; Alternative Cooling System